The Influence Of Educational Background, Accounting Knowledge, Work Experience, And Business Size On The Implementation Of The Accounting Cycle With External Support As A Moderating Variable In Msmes In Kandis Village, Siak Regency - Siburian, Winda Utami Br; Chrisna, Heriyati; Dwilita, Handriyani (Journal of Management, Economic, and Accounting, 2025)
This study aims to provide an overview of the preparation of financial reports by broiler chicken farms based on their compliance with accounting principles and to explain their sources of capital and financial performance. The object of this study is Muhtar Keliat's broiler chicken farm, which operated from February to November 2024. This is a descriptive quantitative study using a case study approach. Data collection was conducted through documentation and analysis of financial reports. The results indicate that the financial reports have been prepared in a simple manner but do not fully comply with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). The business capital is entirely sourced from the owner, with no loans or liabilities. Profit and asset information have been recorded, but cash flow statements and notes to the financial statements have not been included. Challenges encountered in preparing the reports include a lack of accounting understanding and the lack of ongoing guidance in preparing standard-compliant financial reports. This impacts business owners' limited ability to use financial reports as a basis for optimal decision-making. This study aims to analyze the influence of educational background on the implementation of the accounting cycle in Micro, Small, and Medium Enterprises (MSMEs) in Kandis Village, Siak Regency, and to examine the role of external support as a moderating variable. This research employs a quantitative approach, with data collected through questionnaires distributed to MSME actors. Regression analysis results show that educational background has a positive and significant effect on the accounting cycle of MSMEs, as indicated by a t-value of 3.320 > t-table of 2.060 and a significance level of 0.003 < 0.05. However, the interaction test results reveal that external support does not moderate the relationship between educational background and the accounting cycle, with a significance value of 0.811 > 0.05. These findings are consistent with the Theory of Planned Behavior, which states that perceived behavioral control affected in this context by the level of education plays an essential role in shaping individual intention and behavior. Therefore, education is a key factor in enhancing the ability of MSME actors to effectively implement the accounting cycle, regardless of the presence of external support.